A conceptual knowledge transfer model for blockchain technology adoption in wine supply networks: Special Issue "Transforming wine value chains – Adapting to a changing world" - Kramer, Michael Paul; Hanf, Jon H. (Wine Economics and Policy, 2026)
Effective adoption of blockchain technology in supply networks depends significantly on inter-organizational knowledge transfer, particularly in the pre-adoption phase when stakeholders must be convinced of its perceived benefits. This conceptual study introduces the Evolutionary Knowledge Transfer Model (EKTM), a novel framework which explains how explicit and tacit knowledge about blockchain dynamically evolve across vertically coordinated multi-tier wine supply networks. Different to previous models, it integrates dyadic, firm, and network perspectives while highlighting the essential role of tacit knowledge transfer, two aspects often overlooked in existing frameworks. Methodologically, the study adopts the design approach of Jaakkola for conceptual research combining knowledge management, complex network, and strategic management theories. The study contributes to supply chain management literature, demonstrating the crucial role of tacit knowledge transfer in blockchain adoption. It provides managers with a conceptual tool to assess knowledge flow and balance explicit and tacit knowledge transfer with the objective to accelerate technology adoption across the supply network. This study closes a critical gap in understanding how knowledge about disruptive digital technologies evolves in vertically coordinated supply networks.